Logo Kerupuk Mie "Kembang Matahari" dari Prespektif Estetika DeWitt Parker - Rukiah, Yayah; Purnengsih, Iis; Pratama, Dendi; Dawami, Angga Kusuma (Magenta | Official Journal STMK Trisakti, 2019)
Visual identity is the main thing that must be built by an entity to be known to the wider community through appropriate visual communication. The forms of visual communication carried out can take the form of anything, such as logos, corporate identities, to the visual formation of their branding. Visual communication that is constantly being built will make people more familiar with the products or services offered to the community. Mie Kupuk "Kembang Matahari" is trying to shape its visual identity, starting with the logo it made. The method used is descriptive qualitative method with visual analysis of identity. The approach to creativity and aesthetic theory is elaborated to find out more about how the Visual Identity will be built by Crackers Noodle "Kembang Matahari". Through excavation of ideas, construction of corporate identity, overall design, the visual identity to be built by crackers noodle and the making of "Kembang Matahari" is a superior product of the city of Bogor. This paper discusses the visual of a new logo on Crackers Noodle "Kembang Matahari" and the visual identity that the company wants to build by using the aesthetic theory formulated by Parker. This paper concludes that the new logo form that will be used as the visual identity of Crackers Noodle "Kembang Matahari" has the power of ideas that are sufficient to be introduced to the wider community as seen from the principle of Unity, Principle of principle, Principle of variation, Principle of balance, Principle of Development, Principle of Layout seen from the logo of Mie Kupuk "Kembang Matahari".